SIMPLE CONTINGENCY ANALYSIS, PARALLEL COMPENSATION, AND DETERMINATION OF THE LOADING MARGIN IN TRANSMISSION LINES - Cechinel, Bruna Pontes; Oliveira, Cristiane Lionço de; Konopatzki, Evandro André; Marangoni, Filipe; Conceição, Katiani Pereira da (Seven Editora, 2025)
The electrical system needs to be reliable and capable of withstanding contingencies to guarantee energy demand without overloading electrical equipment. In this research, the voltage stability of the STB-33 test system was analyzed in three situations: base case, after simple transmission line contingency simulation, and after applying parallel compensation in cases of contingency with voltage violations. The ANAREDE software was used to simulate contingencies and seek solutions using the Newton-Raphson method, discarding cases where line removal would cause isolation of network elements, resulting in 26 simulated contingency cases. Seven cases did not obtain an initial solution for the load flow, mainly in area A, which is not able to supply its demand alone, resulting in an exchange of energy with area B. As a means of forcing a solution to the load flow, three methods were used: turning off the ANAREDE controls, representing the load at 75% active power, and defining the buses that interconnect the contingency lines as a reference. The last option resulted in the convergence of all cases and the lowest severity indices. These cases were disregarded in the compensation studies due to simplifications to achieve convergence. Contingency cases with flow violations in the lines are mainly in area B, where area A imports energy due to its demand exceeding supply. Cases with voltage violations in the busbars are mostly found in area A, as the buses in this area are unable to support all their demand, resulting in voltage drops. For these cases, parallel compensation was applied, which is important for controlling reactive power in the network and improving the performance of transmission lines. Therefore, FLUPOT was used to perform the optimal power flow calculations, determining the amount of reactive power to be allocated and the buses that should receive parallel compensation. Cases 18 and 22 were chosen to receive compensation due to their high severity indices, where the compensation proved effective, recovering the voltages of the contingent and peripheral busbars. Voltage stability studies identify vulnerable points in the system, and a common method is the PV curve. Using the continuation method through ANAREDE to determine the PV curve and analyze the load margin of cases 18 and 22, a load increase of 0.2% was performed. Some buses did not remain stable in terms of voltage, even after compensation. These buses are considered critical because they presented undervoltage during emergencies. The base case had the highest load margin and voltage safety margin, respecting the minimum limit pre-established by ONS, of 7% for complete systems. Cases 18 and 22, after the contingency, presented a load margin and voltage safety margin below the 4% limit, which is the minimum limit for incomplete systems. After compensation, cases 18 and 22 had an increase in load and voltage indices, with a safety margin of 4.8446% for case 18 and 6.2976% for case 22. DOI: https://doi.org/10.56238/sevened2025.036-028